Pengembangan Video Pembelajaran Berbasis Syafi’iyah Pada Mata Kuliah Fiqih Ibadah - Ilmudinulloh, Rafiud; Kamaru, Fahri Fijrin (Muróbbî: Jurnal Ilmu Pendidikan, 2024)
This research aims to develop a shafi'iyah-based learning video in the course of Fiqih Ibadah. This study uses the ADDIE research design which consists of Analysis, Design, Develop, Implement, and Evaluate. Data were collected through media expert validation questionnaires and field tests and then analyzed using an attitude scale. The results of the study concluded that the syafi'iyah-based learning video was valid and appropriate for use in the course of Fiqih Ibadah. This can be seen from the results of the validity of a media expert with a good average value of 85% or 4.3, the validity of a material expert with a very good average value of 97.1% or 4.9, and field tests with a good average value, 89% or 4.4.